Inhibition, transition, and surge: dynamic evolution of pediatric respiratory pathogen trends amid COVID-19 pandemic policy adjustments - Xu, Xuena; Pan, Zhenzhen; Dong, Heting; Zhang, Yizhu; Xu, Lina; Wang, Pengli; Wang, Yufeng; Li, Jiaoyang; Jiang, Wujun; Hao, Chuangli (Frontiers in Public Health, 2024)
Background The implementation of a zero-COVID policy for 3 years in China during the COVID-19 pandemic significantly impacted a broad spectrum of acute respiratory tract infections (ARTIs). The epidemiological characteristics of ARTI pathogens in children following the cessation of the zero-COVID policy remain unclear. Methods Etiologically diagnostic data from 82,708 children with ARTIs at the Children’s Hospital of Soochow University during 2016–2023 were analyzed for 8 pathogens (human respiratory syncytial virus [HRSV], influenza A [FluA], FluB, human parainfluenza virus [HPIV], adenovirus [ADV], human rhinovirus [HRV], bocavirus [BoV], and mycoplasma pneumoniae [MP]). The changes in respiratory infections in Suzhou, China during the first year (2020, Phase I) and the second and third years of the pandemic (2021–2022, Phase II) and the first year after the end of zero-COVID policy (2023, Phase III) versus that in the pre-pandemic years (2016–2019) were compared. Results When compared with the average pre-pandemic levels, the pathogen-positive rate decreased by 19.27% in Phase I (OR: 0.70; 95% CI: 0.67–0.74), increased by 32.87% in Phase II (OR: 1.78; 95% CI: 1.72–1.84), and increased by 79.16% in Phase III (OR: 4.58; 95% CI: 4.37–4.79). In Phase I, the positive rates of HRSV, FluA, ADV, and MP decreased by 26.72, 58.97, 72.85, and 67.87%, respectively, and the positive rates of FluB, HPIV, HRV, and BoV increased by 86.84, 25, 32.37, and 16.94%, respectively. In Phase III, the positive rates of HRSV, FluA, FluB, HPIV, ADV, and HRV increased by 39.74, 1046.15, 118.42, 116.57, 131.13, and 146.40%, respectively, while the positive rate of BoV decreased by 56.12%. MP was inhibited during the epidemic, and MP showed a delayed outbreak after the ending of the zero-COVID policy. Compared with the average pre-pandemic levels, the MP-positive rate in Phase III increased by 116.7% (OR: 2.86; 95% CI: 2.74–2.99), with the highest increase in 0–1-year-old children. Conclusion The strict and large-scale implementation of the zero-COVID policy in the early stages of the COVID-19 pandemic was the main driving factor for the sharp reduction in the rate of children’s respiratory pathogenic infections. The termination of this policy can cause a resurgence or escalation of pathogenic infections.